2021
DOI: 10.1097/mao.0000000000003280
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor 2 Agonism is Capable of Preventing Lipopolysaccharide Induced Decreases of Cochlear Microcirculation – A Potential Approach for Inner Ear Pathologies

Abstract: Hypothesis:The ability of JWH-133, an agonist at the cannabinoid receptor 2, to abrogate the effects of lipopolysaccharide on cochlear microcirculation was investigated. Background: Cochlear inflammation and subsequent impairment of microcirculation is part of numerous pathologies affecting inner ear function, including suppurative labyrinthitis, noise trauma, and sudden sensorineural hearing loss. One way of causing cochlear inflammation is exposing the cochlea to lipopolysaccharide, a bacterial endotoxin. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The etiology of SSNHL remains unclear, which may be related to hair cell apoptosis and damage caused by inflammatory responses, viral infection, microcirculation disturbance, and other factors, because inflammation can result in microvascular damage [ 25 ], atherosclerosis [ 26 ], and cochlear immune responses [ 27 ]; in vivo experiments have shown that LPS-stimulated guinea pigs have severe cochlear microcirculation disturbance [ 28 ]. Therefore, inflammation is considered to be an important cause of SSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of SSNHL remains unclear, which may be related to hair cell apoptosis and damage caused by inflammatory responses, viral infection, microcirculation disturbance, and other factors, because inflammation can result in microvascular damage [ 25 ], atherosclerosis [ 26 ], and cochlear immune responses [ 27 ]; in vivo experiments have shown that LPS-stimulated guinea pigs have severe cochlear microcirculation disturbance [ 28 ]. Therefore, inflammation is considered to be an important cause of SSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Weiss et al. found that the cannabinoid receptor 2 (CNR2) agonist (JWH‐133) prevented LPS‐induced reductions in the cochlear microcirculation, thereby reducing inflammation in guinea pigs [103] . Kim et al.…”
Section: Potential Therapeutic Targets For Snhlmentioning
confidence: 99%
“…For example, Weiss et al found that the cannabinoid receptor 2 (CNR2) agonist (JWH-133) prevented LPS-induced reductions in the cochlear microcirculation, thereby reducing inflammation in guinea pigs. [103] Kim et al found that immune checkpoints are crucial in regulating immune activation, which is a promising strategy for treating chronic inflammation. Programmed Cell Death Protein-1 (PD-1) monocytes are novel biomarkers and therapeutic targets for cerebral vasospasm following aneurysmal subarachnoid hemorrhages.…”
Section: Potential Therapeutic Targets For Snhlmentioning
confidence: 99%
“…CB2 antagonists reverse this effect ( Ghosh et al, 2018 ). Furthermore, another pharmacological agonist (JWH-133) activates CB2 receptors, produces an anti-inflammatory effect in the inner ear, and increases microcirculation following exposure to bacterial endotoxins ( Weiss et al, 2021 ). Although these results appear promising, they were performed in animal models, and therefore the translational implications for humans are quite limited given the absence of studies in this regard.…”
Section: The Cannabinoid System and The Auditory Pathwaymentioning
confidence: 99%